DUŻO PKT
Działania wymierne

a). [tex]\frac{1}{x} -\frac{3}{2x-4} =\frac{x^{2} +2x-4}{2x^{2}-4x }[/tex]


Odpowiedź :

a)

[tex]\frac{1}{x} -\frac{3}{2x-4} = \frac{x^{2}+2x-4 }{2x^{2} -4x} \\\frac{1}{x} -\frac{3}{2x-4} -\frac{x^{2}+2x-4 }{2x^{2} -4x} = 0\\\frac{1}{x} -\frac{3}{2(x-2)}-\frac{x^{2}+2x-4 }{2x(x-2)} = 0\\\frac{2(x-2) - 3x-(x^{2} +2x-4)}{2x(x-2)}=0 \\\frac{2x-4-3x-x^{2} -2x+4}{2x(x-2)} =0\\\frac{x(-3-x)}{2x(x-2)} =0\\\frac{-3-x}{2(x-2)} =0\\[/tex]

gdy ułamek jest równy 0,licznik musi równać się 0, czyli:

[tex]-3-x=0\\-x=3\\x=3[/tex]